The number "e": Concept, definition, calculation, and accurate formula. Issue 2 (14th April 2019) - Fernández Blanco, Roberto
Abstract : This article demonstrates a new method to determine the digits for the value of " e " Napier's constant or Euler's number. The estimate works out to a single equation. In process safety, several failure probability models use values of " e " to a power. Thus, novel methods to estimate the value of " e " may be of interest to a process safety engineer. © 2019 American Institute of Chemical Engineers Process Saf Prog 38: e12052, 2019